Family socioeconomic status and weight velocity in children aged 6-24 months - Tiara Eka; Julius Anzar; Mutiara Budi Azhar (Paediatrica Indonesiana, 2016)
Background Socioeconomic status is one of the external factors that influences weight velocity.Objective To assess for a correlation between family socioeconomic status and weight velocity.Method This cross-sectional study was performed from October to December 2014. Subjects were patients at community health centers in Palembang, and included by a consecutive sampling technique. Data were collected by interviewing mothers using questionaires. We measured the children’s weight and compared it to the previous weight measurement on the Child Health Card (Kartu Menuju Sehat/KMS). Risk of failure to thrive was determined by plotting increments onto the 2009 WHO Growth Velocity Standards Chart. Data were analyzed by Fisher’s exact and Chi-square tests.Results The 97 respondents consisted of 74 children (76%) with good weight velocity and 23 children (24%) with risk of failure to thrive. Using indicators of socioeconomic status, we found a significant correlation between the level of family welfare and weight velocity. (PR=48.000; 95%CI 2.3 to 997.1; P=0.016). However, level of maternal education (P=0.788) and the number of children in the family (P=0.550) had no significant correlation to weight velocity. Caregivers of children (P= 0.560) and duration of exclusive breastfeeding (P=0.390) were not confounding variables for weight velocity in this study.Conclusion High to moderate level of family welfare is significantly correlated to good weight velocity. However, weight velocity has no significant correlation to either the level of maternal education or the number of children in the family. Caregivers of children and duration of exclusive breastfeeding are not confounding variables for this study.